Abscisic Acid as an Internal Integrator of Multiple Physiological Processes Modulates Leaf Senescence Onset in Arabidopsis thaliana - Song, Yuwei; Xiang, Fuyou; Zhang, Guozeng; Miao, Yuchen; Miao, Chen; Song, Chun-Peng (Frontiers in Plant Science, 2016)
Many studies have shown that exogenous abscisic acid (ABA) promotes leaf abscission and senescence. However, owing to a lack of genetic evidence, ABA function in plant senescence has not been clearly defined. Here, two-leaf early-senescence mutants (eas) that were screened by chlorophyll fluorescence imaging and named eas1-1 and eas1-2 showed high photosynthetic capacity in the early stage of plant growth compared with the wild type. Gene mapping showed that eas1-1 and eas1-2 are two novel ABA2 allelic mutants. Under unstressed conditions, the eas1 mutations caused plant dwarf, early germination, larger stomatal apertures, and early leaf senescence compared with those of the wild type. Flow cytometry assays showed that the cell apoptosis rate in eas1 mutant leaves was higher than that of the wild type after day 30. A significant increase in the transcript levels of several senescence-associated genes, especially SAG12, was observed in eas1 mutant plants in the early stage of plant growth. More importantly, ABA-activated calcium channel activity in plasma membrane and induced the increase of cytoplasmic calcium concentration in guard cells are suppressed due to the mutation of EAS1. In contrast, the eas1 mutants lost chlorophyll and ion leakage significant faster than in the wild type under treatment with calcium channel blocker. Hence, our results indicate that endogenous ABA level is an important factor controlling the onset of leaf senescence through Ca2+ signaling.